Penglihatan Foveal (Foveal Vision) - Mohd Zol, Azida (Universiti Sains Malaysia, 2006)
In the world of globalisation nowadays, rapid expansion in various fields is the main asset for the development of mankind and their civilization. Digital Image Processing also plays an important role in different applications including scientific, industrial, bio-medical, outer space, government sectors and others. The application of digital image processing techniques are widely used in the modern medical field today. Beyond this expansion, digital image processing field move a step forward with the development of a software with the same concept as previously done with human vision capability. This is such a healthy expansion and typically can increase the development of other related fields. This project had succesfully developed an effective software, Foveal Vision that is able to function as an actual human vision system. Fovea is the name for the central part of the retina ("the yellow spot") in our eye. Of the entire surface of the retina, the fovea gives the highest resolution, and therefore the smallest details visible [25]. Robotics and engineering fields are the most probably targetted in demand for the sofware in increasing the ability as well as capability any robotics invention that uses the application of human vision system. It will also help eye specialists to understand the human vision and entirely any related eye diseases can be detected. This software is developed using Borland C++ Builder v5.0 platform with the use of digital image processing concepts and the implementation of appropriate algorithms. Very satisfactory results were obtained from this project after a series of tests were conducted on several grayscale images. It is enough to prove that this software that had been developed is able to create human vision capability as it can function in the same manner like any ordinary human vision does with the input of any grayscale images.